High durabilty bio-polyester resin using graphene and palm oil derivatives for composite appications - Siti Noor Hidayah, Mustapha; Nurbazilah, Thalib (2021)
Research and development of eco-friendly products such as bio-based unsaturated polyester resin helps differentiate product offerings. Graphene‐enhanced fiber‐reinforced biopolymer (gFRP) composites is a new approach in improving the biopolymer properties and applications. Since Malaysia is abundantly available palm oil and natural resources, new approach by blending palm oil and graphene reinforcement is a promising approach to replace the current synthetic product in market.